2020
DOI: 10.3390/jcm9093046
|View full text |Cite
|
Sign up to set email alerts
|

Restless Legs Syndrome During Pregnancy and 12 Weeks Postpartum and Its Links to Cardiovascular Diseases, Stressful Life Events, and Psychiatric History

Abstract: Restless legs syndrome (RLS) is highly prevalent among pregnant women. In the present study, a neurological–obstetrical sample of 561 postpartum women was retrospectively screened for RLS symptoms during pregnancy and in the first 12 weeks postpartum. The first screening took place within 1 to 6 days of delivery (T0) and the second 12 weeks after childbirth (T1). The pregnancy-related RLS prevalence rate was found to be 21% (n = 119), with the women suffering from RLS being more often affected by psychiatric h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…[ 31 ] However, in our study, no significant relationships were seen between RLS during pregnancy and complications and outcomes of pregnancy, including the incidence of emergency LSCS, prematurity, low birthweight, GDM, and PIH, unlike other studies which reported a positive association between RLS and GDM and PIH. [ 32 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 ] However, in our study, no significant relationships were seen between RLS during pregnancy and complications and outcomes of pregnancy, including the incidence of emergency LSCS, prematurity, low birthweight, GDM, and PIH, unlike other studies which reported a positive association between RLS and GDM and PIH. [ 32 ]…”
Section: Discussionmentioning
confidence: 99%
“…The primary occurrence of RLS during pregnancy represents a risk factor for developing RLS later in life (4‐fold increase) or in the following pregnancies. European Research Groups in Switzerland, Italy, Slovakia, Germany published in the past years new data regarding the prevalence and management of RLS during pregnancy (Cesnik et al, 2010; Garbazza & Manconi, 2018; Goecke, Schnakenberg, Frensch, & Chechko, 2020; Manconi et al, 2004; Minar, Habanova, Rusnak, Planck, & Valkovic, 2013; Silvestri & Aricò, 2019).…”
Section: Epidemiology Of Rlsmentioning
confidence: 99%
“…RLS is associated with various pregnancy complications, including pregnancy-induced hypertension (6)(7)(8), cardiovascular disease (6)(7)(8)(9), gestational diabetes (10,11), sleep disorders (12, 13), poor quality of life, and depression (14)(15)(16). These issues can contribute to adverse pregnancy outcomes such as preterm birth (17, 18), miscarriage (19), low birth weight (8,18), postpartum depression (20), and baby blues (9). Furthermore, RLS increases the risk of recurrence, chronicity, and cardiovascular disease (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Factors associated with RLS include female gender, pregnancy, lower socioeconomic status, poor health, low iron levels, and advanced age, comorbidity with Parkinson's disease or psychiatric disorders, and family history of similar disorders (16,32). During pregnancy, variables such as taking prophylactic iron supplementation (11, 33), a history of premenstrual syndrome (9), chronic diabetes mellitus (21), later gestational age (34), poor sleep quality, stressful life events, and excessive daytime sleepiness (7) have also been associated with RLS.…”
Section: Introductionmentioning
confidence: 99%